PENGARUH ENTREPRENEURIAL EDUCATION TERHADAP ENTREPRENEURIAL INTENTION DENGAN SELF-EFFICACY SEBAGAI VARIABEL INTERVENING PADA MAHASISWA DI KABUPATEN BANYUMAS - Pebriyanti, Nungki; Rizky, Gia (Jurnal EMT KITA, 2024)
This study aims to analyze the effect of entrepreneurial education on entrepreneurial intention with self-efficacy as an intervening variable for students in Banyumas Regency. The sampling technique in this study used purposive sampling, with a total of 105 student respondents. Primary data in this study were collected using a questionnaire through a Google Form that has been tested for validity and reliability. Data analysis in this study used descriptive analysis tests, instrument tests (validity and reliability tests), classical assumption tests (normality, linearity, and heteroscedasticity), simple regression equation tests, and hypothesis testing (t-test, coefficient of determination, and path analysis) with the help of IBM SPSS Statistics program version 25. The results showed that entrepreneurial education has a positive and significant effect on entrepreneurial intention, entrepreneurial education has a positive and significant effect on self-efficacy, self-efficacy has a positive and significant effect on entrepreneurial intention, and self-efficacy partially mediates the relationship between entrepreneurial education and entrepreneurial intention.